Marketizing education: a microanalytic account. - Cohen, Etan (Discourse: Studies in the Cultural Politics of Education, 2024)
The neoliberal turn has driven attempts to marketize education, but how does marketization occur? In this article I draw on ethnographic and linguistic-ethnographic methods to investigate marketization through a microanalytic lens. My investigation focuses on a team of educational professionals, who participated in a workshop led by an organizational consultant named Eric. During the workshop, Eric successfully encouraged the educators to adopt some key business terms that he imported from the high-tech sector. My findings indicate that the marketization of education was not straightforward. Rather, the process encountered some resistance and sowed confusion before a business discourse ultimately took hold. The process of marketization became entangled with the power dynamics shaped by group members' positioning vis-à-vis one another; and furthermore, it required the group to negotiate the meaning of some key terms. Marketization was ultimately mediated by a cognitive device called the Business Model Canvas and it relied on some pre-existing neoliberal tendencies among the workshop's participants.